2006
DOI: 10.1158/0008-5472.can-05-3055
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Determining Region Y Box 4 Is a Transforming Oncogene in Human Prostate Cancer Cells

Abstract: Prostate cancer is the most commonly diagnosed noncutaneous neoplasm and second most common cause of cancerrelated mortality in western men. To investigate the mechanisms of prostate cancer development and progression, we did expression profiling of human prostate cancer and benign tissues. We show that the SOX4 is overexpressed in prostate tumor samples compared with benign tissues by microarray analysis, real-time PCR, and immunohistochemistry. We also show that SOX4 expression is highly correlated with Glea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
217
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(233 citation statements)
references
References 43 publications
14
217
2
Order By: Relevance
“…Although the importance of several SOX family proteins is well characterized in vertebrate developmental processes (Bowles et al, 2000), fully defined SOX target genes are few. There are four known SOX4 targets, p56 lck , CD2, TLE1 and PUMA but the SOX4 binding motifs for only p56 lck and CD2 are known (Wotton et al, 1995;McCracken et al, 1997;Liu et al, 2006). This study is the first to report 31 experimentally confirmed direct target genes for SOX4 in one publication.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although the importance of several SOX family proteins is well characterized in vertebrate developmental processes (Bowles et al, 2000), fully defined SOX target genes are few. There are four known SOX4 targets, p56 lck , CD2, TLE1 and PUMA but the SOX4 binding motifs for only p56 lck and CD2 are known (Wotton et al, 1995;McCracken et al, 1997;Liu et al, 2006). This study is the first to report 31 experimentally confirmed direct target genes for SOX4 in one publication.…”
Section: Discussionmentioning
confidence: 78%
“…Empirical evidence suggested that SOX4 plays an important function in liver tumor metastasis as RNAi knockdown reduced HCC cell migration, invasion and intrahepatic metastasis in an orthotopic liver cancer model. This SOX4 function also seems to operate during breast cancer metastasis (Tavazoie et al, 2008) but not in other human cancer types (Aaboe et al, 2006;Liu et al, 2006;Pramoonjago et al, 2006). This suggests that SOX4 has diverse activities across various human cancers and that these are likely to be cell context-dependent, involving differential target activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Recently, the overexpression of SOX4 has been reported in several tumors, including prostate cancer, breast cancer and colon cancer. [18][19][20] It has well documented that SOX4 stabilizes b-catenin, and increases Wnt signaling pathway in many types of cancers. 21 Taking together it seems that SOX4 transcription factor plays an vital role in Wnt signaling pathways in TNBC 14,22 Aberrant Fzd7 expression is found in different types of human cancers.…”
Section: Introductionmentioning
confidence: 99%